Attitude towards the elderly among healthcare related students in Malaysia - Damulak, Panmial P.; Minhat, Halimatus Sakdiah; A. Rahman, Anita (2015)
The focus of this study was to determine the attitude towards the elderly among healthcare related students in Malaysia. The Cross-sectional survey design (CSD) was used for the study. A total of 63 nursing students and 456 medicine students were drawn by stratified random sampling from University Putra Malaysia. Data was collected using a validated modified standard questionnaire consisting of socio-demographic characteristics, Kogan’s Attitude Towards Old People Scale, Facts on Ageing Quiz 2, filial responsibility questionnaire, experience living with elderly questions as well as questions on exposure to geriatric module. Data generated were subjected to statistics of frequency count, percentage and chi-square. The results showed that the mean attitude score was 37.82± 5.641 with overall attitude being negative (52.0%). Mean filial score was 30.10±5.387, and students had low filial responsibility (53.0%), although there was no exposure to geriatric module (54.1%), nevertheless students had a good knowledge of ageing (74%), 70.3% are currently living with the elderly while 74.0% previously lived with the elderly. Furthermore, there was significant association between attitude towards the elderly and filial responsibility (x^2 = 44.599, p = 0.001), age (x^2= 11.518, p = 0.042) and year of study (x^2= 12.699, p = 0.031). Consequently, it was concluded that the attitude towards the elderly is significantly associated with low filial responsibility, age, year of study and nursing home visit with the recommendation that geriatric components should be improved and included at every stage of healthcare professional training.